ANTIMICROBIAL ACTIVITY OF KERSEN (Muntingia calabura L.) LEAVES: A SYSTEMATIC REVIEW - Diah Ulfa Hidayati; Runjati Runjati (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Many kinds of antibiotics are being used for treating the infections, but bacterial resistance is a main therapeutic problem. Medicinal plants are one of sources of therapeutic aid for relieve human illness.Muntingia Calabura is a medicinal plant that might have pharmacological value. Muntingia Calabura, is called throughout the world as “Jamaican cherry” and in Indonesia, it is known as “Kersen” or “Talok”. This study aims to analyze the antimicrobial activity of Muntingia calabura leaves.Methodology: This systematic review was conducted from December 2018 to February 2019 using PRISMA reporting guidelines. Literature has been retrieved from MEDLINE, Science Direct, Google Scholar, PubMed, Springer Link, and IEEE Xplore, use key words Muntingia calabura, phytochemical, pharmacological, and antimicrobial. The articles written by English.Results: From 9 studies, the antibacterial test for Muntingia calabura leaves was carried out on 18 types of microorganisms. Muntingia calabura leaves proved to be effective against S. aureus and P. aeruginosa bacteria. 4 studies showed negative results use Muntingia calabura in certain types of bacteria.Conclusion: Therefore, this plant can be used for treatment of bacteria. This study is also presented to help guide researchers to plan their future studies related to this plant for preventing the bacterial infection, especially in obstetrics and gynecology.